The Role of Entrepreneur Motivation: The Mediation of Entrepreneur Orientation on Company Performance - Moko, Wahdiyat; Wati, Cicik R; Basuki, Ananto; Bintoro, Nugroho Suryo; Barinta, Dunga Dwi (Profesional Muda Cendekia Publishing, 2024)
Research Aims: The main focus of this research is to determine the role of entrepreneurial motivation as a mediator in the relationship between entrepreneurial orientation and Company Performance. Design/methodology/approach: This study uses an explanatory research approach with micro-enterprises run by beneficiary families of the Program Keluarga-Harapan (KPM-PKH) in Malang City as research objects. Data collection for this research was carried out by distributing 300 questionnaires online, but only 261 questionnaires were returned and declared valid for testing research data. The data analysis was carried out using SEM-PLS. Research Findings: This study's results indicate a relationship between entrepreneurial orientation, entrepreneurial motivation, and Company Performance. This study also found that entrepreneurial motivation perfectly mediates the relationship between entrepreneurial orientation and Company Performance. Entrepreneurial motivation plays an essential role in connecting to improve performance when business actors do not really have a good enough business orientation. The motivation of business actors will help business actors to remain enthusiastic to try again and again when business actors face failure in the process of increasing business sales. Theoretical Contribution/Originality: The theoretical contribution of the research on